A Study of Mechanical and Wear Behavior of SiC-CeO2 Reinforced Al7075 Hot Rolled Hybrid Composites - M. Ravikumar; R. Naik; R. Suresh; K.Y. Chethana (Archives of Metallurgy and Materials)
Fabrication of aluminium (Al) composites by stir casting process is an effective method for fabrication of better quality of Metal Matrix Composites (MMCs). Stir casting technique is one of the most commonly accepted techniques. In this research work, Al7075 / SiC+CeO2 hybrid MMCs have been fabricated with varying wt.% of SiC (2%, 4%, 6% and 8%) particulates and constant 5% of CeO2 particulates. The ascast alloy and hybrid composite were hot rolled at a temperature of 500°C. Whereas, both the ascast and hot rolled hybrid composite was subjected to micro-structural, mechanical and wear tests. Optical microscope analysis revealed uniform dispersal of hard particles with in the base matrix in case of both of ascast and hot rolled composites. Hot rolled MMCs showed enhancement of 22.64% of hardness when compared with ascast alloy with increasing reinforcement of 0-6 wt.% of SiC content. Tensile strength increases by 28.24% for hot rolled composites when compared to the as cast and other hybrid composites. Reduction of wear loss by 54.38% for hot rolled composites when compared to the as cast and other hybrid composites. A tensile and wear fractography result shows the internal fractured structure which was analysed using a SEM analysis